Revisiting Glycogen in Cancer: A Conspicuous and Targetable Enabler of Malignant Transformation - Khan, Tashbib; Sullivan, Mitchell A.; Gunter, Jennifer H.; Kryza, Thomas; Lyons, Nicholas; He, Yaowu; Hooper, John D. (Frontiers in Oncology, 2020)
Once thought to be exclusively a storage hub for glucose, glycogen is now known to be essential in a range of physiological processes and pathological conditions. Glycogen lies at the nexus of diverse processes that promote malignancy including proliferation, migration, invasion, and chemoresistance of cancer cells. It is also implicated in processes associated with the tumor microenvironment such as immune cell effector function and crosstalk with cancer-associated fibroblasts to promote metastasis. The enzymes of glycogen metabolism are dysregulated in a wide variety of malignancies, including cancers of the kidney, ovary, lung, bladder, liver, blood and breast. Understanding and targeting glycogen metabolism in cancer presents a promising but under-explored therapeutic avenue. In this review we summarize the current literature on the role of glycogen in cancer progression and discuss its potential as a therapeutic target for cancer treatment.